Pengaruh Perencanaan Pajak dan Profitabilitas Terhadap Nilai Perusahaan dengan BOD Diversity sebagai Variabel Moderasi - Yuli Dwi Astuti; Giawan Nur Fitria (Faculty of Economic and Business, 2019)
This study aims to determine the effect of tax planning and profitability on firm value with BOD diversity as a moderating variable. This research is motivated by the importance of information about the factors that can affect the value of the company. Company value in this study used price book value as an indicator of measurement. The population of this research is the property and real estate sector companies in companies listed on the Indonesia Stock Exchange in 2016 - 2018. The sample of this research is 30 issuers or 90 company financial statement data used in this study. This study uses multiple linear regressiosn with statistical tests and moderate regression analysis test with SPSS 23. The results of this study are tax planning and profitability have a positive and significant effect on firm value. Whereas BOD Diversity weakens the relationship between tax planning and profitability on firm value.